A Structured Approach to Involve Stakeholders in Prioritising Topics for Systematic Reviews in Public Health - Dyon Hoekstra; Dyon Hoekstra; Dyon Hoekstra; Margot Mütsch; Annegret Borchard; Annegret Borchard; Christina Kien; Christina Kien; Ursula Griebler; Ursula Griebler; Erik Von Elm; Eva Rehfuess; et al. (Frontiers Media S.A., 2024)
ObjectivesThis study aimed to develop and apply a structured approach for prioritising topics for systematic reviews in public health, framed according to the readily applicable PICO format, which encourages the involvement of stakeholders' preferences in a transparent matter.MethodsWe developed a multi-stage process, consisting of a scoping and two Delphi stages with web-based surveys and invited public health stakeholders in Switzerland to participate: First, respondents specified topics for different public health domains, which were reformulated in a PICO format by content analysis. Second, respondents rated the topics using five stakeholder-refined assessment criteria. Overall rankings were calculated to assess differences between stakeholder groups and rating criteria.ResultsIn total, 215 respondents suggested 728 topics altogether. The response rate in the two Delphi stages was 91.6% and 77.6%, respectively. Most top-rated review topics focused on the effectiveness of interventions providing education to different target groups, followed by interventions to increase access to specific healthcare services.ConclusionOur approach encourages involvement of stakeholders in identifying priorities for systematic reviews and highlights disparities between stakeholders and between individual criteria.